2007
DOI: 10.1192/apt.bp.106.003434
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and psychosis: the origins and implications of an association

Abstract: Evidence for the effectiveness of treatment or secondary prevention of psychotic illness such as schizophrenia is often disappointing. This situation reflects our limited understanding of the aetiology of psychosis. There is good evidence that both genetic and environmental factors are implicated but the precise identity of these is unclear. Cannabis use is one candidate as a possible, modifiable environmental influence on both incidence and prognosis of psychosis. Evidence supporting this candidature is exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…2 Although the association of cannabis use and severe mental illness has been reported in Africa for years, it is only recently that this association has been established internationally. 63,64 Cannabis is the third most frequently used substance by youths in Africa and up to 12-40% of young people admitted to psychiatric hospitals in Africa are diagnosed with cannabis or drug-induced psychosis. 8,65 Interventions with young people to reduce substance use could lessen the costs of mental health treatment and protect the mental health of thousands of young people in Africa.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…2 Although the association of cannabis use and severe mental illness has been reported in Africa for years, it is only recently that this association has been established internationally. 63,64 Cannabis is the third most frequently used substance by youths in Africa and up to 12-40% of young people admitted to psychiatric hospitals in Africa are diagnosed with cannabis or drug-induced psychosis. 8,65 Interventions with young people to reduce substance use could lessen the costs of mental health treatment and protect the mental health of thousands of young people in Africa.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Macleod, however, writing in Advances in Psychiatric Treatment, critically examined the scientific evidence of a causal association between cannabis use and psychosis and concluded that, at present, evidence for this association is not strong. Nevertheless, he calls for better observational and genetic studies and for interventions targeting cannabis use, especially in the young (Macleod, 2007).…”
Section: Atakanmentioning
confidence: 99%
“…This logic is spurious as cannabis is clearly not the only factor that causes psychosis and the impact of cannabis will be muted if the potency of some of the other factors has declined. Others who are skeptical about the evidence that cannabis is a cause of schizophrenia argue that the relationship is modest in size and can be explained by confounding variables and noncausal mechanisms [51,52].…”
Section: Cannabis Use and Schizophrenic Symptomsmentioning
confidence: 99%